2000
DOI: 10.1021/bi000750l
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Role of the Fe−S Subunit Hinge Region during Qo Site Catalysis in Rhodobacter capsulatus bc1 Complex

Abstract: The ubihydroquinone:cytochrome c oxidoreductase, or bc(1) complex, functions according to a mechanism known as the modified Q cycle. Recent crystallographic data have revealed that the extrinsic domain containing the [2Fe2S] cluster of the Fe-S subunit of this enzyme occupies different positions in various crystal forms, suggesting that this subunit may move during ubihydroquinone oxidation. As in these structures the hydrophobic membrane anchor of the Fe-S subunit remains at the same position, the movement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
79
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(86 citation statements)
references
References 27 publications
6
79
1
Order By: Relevance
“…All R. capsulatus strains were grown in mineral-peptone-yeast-extract enriched media (MPYE) under semi-aerobic conditions in the dark at 35° C, as described previously (10). The construction and growth phenotypes of the H212N and H217L, D and R mutants have been described previously in (8,10,22), respectively.…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…All R. capsulatus strains were grown in mineral-peptone-yeast-extract enriched media (MPYE) under semi-aerobic conditions in the dark at 35° C, as described previously (10). The construction and growth phenotypes of the H212N and H217L, D and R mutants have been described previously in (8,10,22), respectively.…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%
“…The construction and growth phenotypes of the H212N and H217L, D and R mutants have been described previously in (8,10,22), respectively.…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…that introduction of excess flexibility by substitution with 6 Gly residues (19) or of extra length by insertion of 1 or more residues (17,24,26) in the hinge region is deleterious to the function of the bc 1 complex (Table III, parts A and B). With 4 -7 glycine residues in the sequence, the ISP hinge region in the b 6 f complex is predicted to be structure-less and more flexible than that in the bc 1 complex (Table I).…”
Section: Consequences Of Increased Flexibility and Length Of The Hingmentioning
confidence: 99%
“…It was subsequently found that the function of the complex is very sensitive to perturbation of the sequence and structure of the hinge region by sitedirected mutagenesis in which the hinge was altered by residue deletion, insertion, and substitution (17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Although these data were interpreted in terms of a requirement for the mobility of the ISP soluble domain, the extreme sensitivity of bc 1 function to increases in hinge flexibility (19) and length (17,24,26) cannot be predicted or inferred from the x-ray structure data. Thus, it is of interest to study the function of the putative hinge region in the b 6 f complex (Table I).…”
mentioning
confidence: 99%